Benefícios e desafios da tutoria por pares para aluno com deficiência intelectual - Marins, Kéren-Hapuque Cabral de (Universidade Federal de São Carlos, 2019)
The search for teaching strategies that provide more learning and participation from the Special Education Target Audience (SETA) in the learning context is a challenge for teachers and schools. Among these possibilities, this research is based on Peer Tutoring (PT) where the strategy involves both academic performance and intersocial relationships, capable of meeting diversity, finding on the tutor student a teaching instrument, which interacts with a classmate, the tutored one. Based on a qualitative approach this research has essential enforcement and when it comes to the procedure, field research. The commonplace goal was to elaborate, develop and evaluate a PT program on Intellectual Disability (ID) around the classroom of an elementary school – late graduation grades and specific goals, analyze and evaluate the results of this strategy for the participation by the ID student, on tutor and tutored relationship, on the expectations from tutors and teachers involved in the tutorial action and its impressions, understandings and feelings from it after the attendance of the involved ones. The study took part at a state public school located in a small town from the countryside of São Paulo State. Engaged in this study an ID student, three tutor students, a Portuguese Language and a Math teachers. The data collection procedure had five primaries observations sessions plus thirty others continuous observations sessions, registered in notes fields, eight tutoring meetings that took place during the program and six starting as six concluding interviews with all participants. In the data analysis was adopted the technique of Content Analysis with ten established categories. The results showed that, when organized and integrated into the daily classroom dynamics, the PT strategy contributed to the inclusion of the ID student, leveling the interactions involving the peers and teachers and his responsiveness to the proposed activities, resulting in an increased participation of the classroom environment. The results presented three topics that deserve better elaboration for the maintenance of the PT strategy: 1) the amount of selected and trained tutors must attend the minimal number necessary to avoid making them overloaded; 2) is necessary to elaborate strategies to decrease the frequency of intervention due to the dependence that the tutee establishes; 3) the affinity from the tutor to the tutored, same should be considered to reach the teacher who will carry out the strategy. The intention with this research is to describe the process of implementing a strategy to meet the diversity and contribute to the practice from the teachers, contributing to the changeover of the paradigm which sets the teacher as the only one responsible to the learning and development of the SETA student. It is a conversion of perspective when establishing that the students themselves may assist the teacher in mediating academic and social skills in class. Likewise, there is an effort to contribute theoretically and practically to the development of PT in the Brazilian educational condition.
Benefits and challenges of peer tutoring for students with intellectual disabilities
Keywords: Educação especial; Deficiência intelectual; Tutoria por pares; Special education; Intellectual disability; Peer tutoring; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM